2022
DOI: 10.1002/ccr3.5475
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected difficult airway due to an undiagnosed congenital lingual thyroglossal duct cyst in a neonate without stridor: A case report

Abstract: Lingual thyroglossal duct cysts can be a rare cause of feeding difficulties in infants. Here, we describe a case of an infant with vomiting and feeding difficulty diagnosed with Hirschsprung's disease. However, she developed an unexpected difficult airway during anesthesia induction due to an undiagnosed lingual thyroglossal duct cyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…12 It has been reported that 7% of the population has TC worldwide. 13 Controversy exists in the literature about demographic distribution of TC at the time of diagnosis. In a metaanalysis, Allard reported 31.5% patients under 10 years of age, 20.4% during their 2 nd decade, 13.5% in their 3 rd decade of life and 34.6% were reported older than 30 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…12 It has been reported that 7% of the population has TC worldwide. 13 Controversy exists in the literature about demographic distribution of TC at the time of diagnosis. In a metaanalysis, Allard reported 31.5% patients under 10 years of age, 20.4% during their 2 nd decade, 13.5% in their 3 rd decade of life and 34.6% were reported older than 30 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…The lesion usually appears in the median line of the neck in its upper 1/3 part and rarely occurs at the base of the tongue (around 2.1%) [6,7], the suprasternal notch (approximately 10%) [8], or within the thyroid gland parenchyma [9]. It presents as a smooth, painless, and soft growth occurring in the neck at the thyrohyoid membrane level, with proximity to the adjacent hyoid bone [10].…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms depend on the location and size of the lesion and may include dyspnea, dysphagia, or speech difficulties [7]. The presence of a lesion based on the base of the tongue can be hazardous due to potential obstruction of the laryngeal and pharyngeal airways..…”
Section: Discussionmentioning
confidence: 99%